THE ROLE OF COMMITTEE IN MANAGE RESOLVING MEDICAL - Nini Deritana; Redyanto Sidi; Bambang Fitriyanto (SEAN Institute, 2023)
As in the case of Medical Dispute Resolution who is a figure responsible for the implementation of good clinical governance to improve staff professionalism, maintain the quality of the staff profession, maintain discipline, ethics, and professional behavior of medical staff. In addition to the hospital director. So, the main door in the event of a medical dispute is the Ethics Committee. Why medical disputes occur and how the role of the medical committee in it is the problem discussed in this study. This research was conducted using an empirical and sociological approach, namely by discussing the perspective of the law and the social aspects that surround the legal symptoms. The results showed that the application of hospital internal regulations (hospital by laws) at the Abdul Manan HAM Kisaran house has not been implemented properly. Based on the HBL preparation regulations, hospitals need to review and evaluate the HBL owned by the hospital so that it is always relevant and follows the development and needs of the hospital.